Current Induced Heat Generation in Ferromagnet-Quantum Dot-Ferromagnet System - Zhao, Lili (Materials (Basel), 2015)
We study the heat generation in ferromagnet-quantum dot-ferromagnet system by the non-equilibrium Green’s functions method. Heat generation under the influence of ferromagnet leads is very different compared with a system with normal metal leads. The significant effects in heat generation are caused by the polarization angle θ associated with the orientation of polarized magnetic moment of electron in the ferromagnetic terminals. From the study of heat generation versus source drain bias (Q-eV) curves, we find that the heat generation decreases as θ increases from 0 to 0.7π. The heat generation versus gate voltage (Q-eV(g)) curves also display interesting behavior with increasing polarization angle θ. Meanwhile, heat generation is influenced by the relative angle θ of magnetic moment in the ferromagnetic leads. These results will provide theories to this quantum dot system as a new material of spintronics.